Art performance as a builder of student motivation in learning at SD Negeri 2 Cantigi Kulon - Widi Eka Yulita (Universitas Pendidikan Indonesia, 2023)
Kampus Mengajar is part of the Merdeka Belajar Kampus Merdeka (MBKM) program. Kampus Mengajar activities are expected to positively impact the program’s implementation, including SD Negeri 2 Cantigi Kulon. Activities in the Kampus Mengajar program have various work programs, both required for the Kampus Mengajar program and additional work programs based on needs at placement schools. At SD Negeri 2 Cantigi Kulon, one of the different work programs implemented is the art performance work program. This activity aims to rebuild student motivation in learning within the scope of the SD Negeri 2 Cantigi Kulon through a series of “Perpisahan dan Pentas Seni”. The program method used is mentoring by presenting articles in a qualitative descriptive approach. All grade 6 students attended this event, the Head of Cantigi Village, the Committee of SD Negeri 2 Cantigi Kulon, the Head of SD Negeri 2 Cantigi Kulon, all parents or family of grade 6 students, and all students at SD Negeri 2 Cantigi Kulon. The event went according to the planned activities through a series of exercises and efforts made by the students and the Kampus Mengajar student team at SD Negeri 2 Cantigi Kulon. Students looked enthusiastic and enthusiastic in participating in a series of activities, from preparatory exercises to carrying out the event. The students seemed to show seriousness and activeness in learning dance movements. It is hoped that in the future, the school can continue learning dance and activities that can provide a platform for students to show their activeness in activities at school. Abstrak Kampus Mengajar merupakan bagian dari program Merdeka Belajar Kampus Merdeka (MBKM). Kegiatan Kampus Mengajar tentu diharapkan dapat memberikan dampak positif pada tempat pelaksanaan program salah satunya yaitu SD Negeri 2 Cantigi Kulon. Kegiatan pada program Kampus Mengajar ini memiliki berbagai program kerja baik program kerja yang diwajibkan pada program Kampus Mengajar, maupun program kerja tambahan berdasarkan kebutuhan di sekolah penempatan. Di SD Negeri 2 Cantigi Kulon, salah satu program kerja tambahan yang dilaksanakan yaitu program kerja pentas seni. Tujuan dilaksanakannya kegiatan ini untuk dapat membangun kembali motivasi siswa dalam pembelajaran di lingkup SD Negeri 2 Cantigi Kulon melalui rangkaian